(3cJGH GdefgL GdShi hGdefgd GdQhi aj GdWH GdfHhis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO agPG cJGH LeYJ ajg GdCMGOjK GdhGQOI ai GdWH eQJHI Ydi GdCHhGH hChQOJ ajg LejY eG hQO UMjMkG hMSfkG hVYjakG djfJaY Hg ChdhG GdCdHGH s
(3BNQgG (B:s
(3hCNQL GHf GdSfi hCHh fYje Yf YQhI GHf GdRHjQ bGd bdJ dYGFTI jG NGdI ef Cjf dc GdWH bGdJ jG GHf CNJi cGf jQV GdfGS ef Cgdi ajfYJ dg QShd Gddg Udi Gddg Ydjg hSde aCYjg aCfYJg ddfGS Je hced HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs